166 The correlation between working conditions and health status of nursing personnel in nursing homes in Taiwan. (11th October 2013) - Lin, L; Judith, SC; Leon, Yue
Abstract : Objectives: To understand working conditions and potential occupational hazards among nursing personnel (registered nurses and nursing assistants) of nursing homes. Methods: A self-administered questionnaire was used to identify the hazards in nursing homes. Chinese Job Content Questionnaire, Chinese Copenhagen Burnout Inventory, and Chinese Nordic Musculoskeletal Questionnaire were used to measure the health status of nursing personnel. An expert focus group and two field visits to nursing home were performed to better understand the potential occupational hazards of nursing homes. Results: A total of 477 eligible questionnaires were completed and returned for final analysis. For biological hazards, needlestick injuries were associated with high job strain of registered nurses. In regard to psychosocial hazards, for registered nurses, low level of employment security was associated with high personal burnout. For nursing assistants, it was associated with high personal burnout, work burnout, and client burnout. Low level of workplace justice was the risk factor for high personal burnout, work burnout of nursing personnel. For ergonomic hazards, the prevalence of musculoskeletal discomforts was 94.8%. Standing ≥ 6 hours was highly associated with high job strain for registered nurses. Twisting waist ≥ 20 times during work was also related to musculoskeletal discomforts in the past year. Conclusions: This study has identified that the work environment of nursing homes would affect health status of nursing personnel in different aspects. To minimise those health effects on nursing home staff, improving the working environment practically and designing educational programs in preventing occupationally induced harms are warranted. A periodical evaluation system is also suggested, to better understand the psychosocial conditions of nursing home staff.